Differences in bioavailability and cognitive-enhancing activity exerted by different crystal polymorphs of latrepirdine (Dimebon®) - Gorin, Boris I.; Tukhovskaya, Elena A.; Ismailova, Alina M.; Slashcheva, Gulsara A.; Lenina, Oksana A.; Petrov, Konstantin A.; Kazeev, Ilya V.; Murashev, Arkady N. (Frontiers in Pharmacology, 2023)
Pharmacokinetic characteristics as well as cognitive-enhancing nootropic activity of latrepirdine (Dimebon®) in relationship with its polymorphic forms have been studied in SD and Wistar rats. It was shown that the crystalline structure (polymorphism) has direct impact on latrepirdine bioavailability and pharmacological activity. A new polymorph of latrepirdine with enhanced pharmaceutical properties, namely Polymorph E, has been discovered.